2018
DOI: 10.1097/mpg.0000000000001942
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Status and Nutritional Intake in 0‐ to 2‐Year‐old Children Consuming a Cows’ Milk Exclusion Diet

Abstract: Objectives:To study micronutrient status and nutritional intake from complementary feeding in children on a cows’ milk exclusion (CME) diet.Methods:Fifty-seven children with cows’ milk allergy, younger than 2 years, were included in a cross-sectional study. Blood was analyzed for micronutrient status. Complementary feeding was defined as all solids and liquids except of breast milk, and assessed by 3-day food diary. The results were analyzed according to 3 feeding patterns: mainly breast-fed (mBF), partially b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
2
19
0
2
Order By: Relevance
“…Nevertheless, there are some important messages from these studies: micronutrient deficiencies do frequently occur in food allergic children and these may include nutrients that have not received significant attention (ie iodine, zinc and vitamin B12) in nutritional assessment in the past. In addition to this, in those studies that have performed both dietary analysis and blood markers, there is often a poor correlation between dietary intake and actual deficiency . In early childhood, breastfeeding, vs hypoallergenic formula (without/without lactose) vs mixed feeding may also impact on the micronutrient status .…”
Section: Micronutrient Deficienciesmentioning
confidence: 99%
“…Nevertheless, there are some important messages from these studies: micronutrient deficiencies do frequently occur in food allergic children and these may include nutrients that have not received significant attention (ie iodine, zinc and vitamin B12) in nutritional assessment in the past. In addition to this, in those studies that have performed both dietary analysis and blood markers, there is often a poor correlation between dietary intake and actual deficiency . In early childhood, breastfeeding, vs hypoallergenic formula (without/without lactose) vs mixed feeding may also impact on the micronutrient status .…”
Section: Micronutrient Deficienciesmentioning
confidence: 99%
“…In view of the limitations of MMA, such as the high cost of analysis, the need for gas chromatography mass spectrometry, and especially in developing countries, the possibility of concentrations being increased by bacterial overgrowth [17], in this study, both serum vitamin B 12 and tHcy were selected as the biological basis for the assessment of the vitamin B 12 status of toddlers. The metabolic conversion of tHcy to methionine is inhibited if the coenzyme methionine synthase is not saturated with vitamin B 12 , leading to the accumulation of tHcy [18]. The results of this study showed that the serum vitamin B 12 level of young children was negatively correlated with tHcy.…”
Section: Discussionmentioning
confidence: 82%
“…According to the World Health Organization (WHO) [12, 16, 17], serum vitamin B 12 concentrations of < 200 pg/mL, 200–300 pg/mL and > 300 pg/mL were used to classify individuals as deficient, marginally deficient, or adequate, respectively. However, stand-alone marker of serum vitamin B 12 has been proven insufficient for the unequivocal diagnosis of vitamin B 12 deficiency [18]. Therefore, a tHcy concentration of > 12 μmol/L was also used to obtain a correct diagnosis, based on the suggestions in the recent literature [1].…”
Section: Methodsmentioning
confidence: 99%
“…Causative factors include prolonged dietary restrictions as part of a single or multiple allergen avoidance, associated feeding difficulties, and atopic comorbidities, rather than differences in energy expenditure or nutritional needs [ 18 19 20 21 ]. Moreover, infants and young children receiving an unsupervised cow's milk exclusion diet have an increased risk of micronutrient deficiencies, mainly due to insufficient iron, calcium, and vitamin B12 intake [ 17 22 ].…”
Section: Introductionmentioning
confidence: 99%